Perioperative blood transfusions and survival in resected pancreatic adenocarcinoma patients given multimodality therapy. Issue 8 (16th August 2021) - Newhook, Timothy E.; Prakash, Laura R.; Soliz, Jose; Hancher‐Hodges, Shannon; Speer, B. Bryce; Wilks, Jonathan A.; Bruno, Morgan L.; Dewhurst, Whitney L.; Arvide, Elsa M.; Maxwell, Jessica E.; Ikoma, Naruhiko; Kim, Michael P.; et al.
Abstract: Background and Objectives: The impact of perioperative blood transfusion (PBT) on outcomes for pancreatic ductal adenocarcinoma (PDAC) patients given multimodality therapy (MMT) remains undefined. We sought to evaluate the association of PBT with survival after PDAC resection. Methods: Pancreatectomy patients (July 2011–December 2017) who received MMT were abstracted from a prospective database. Overall survival (OS) was compared by PBT within 30 days, 24 h (24HR‐BT), or 24 h until 30 days (Postop‐BT). Results: Most (76.6%) of 312 MMT patients underwent neoadjuvant therapy (NT). Eighty‐nine patients (28.5%) received PBT; 58 (18.6%) 24HR‐BT, and 31 (9.9%) Postop‐BT. Compared with surgery‐first, NT patients received more 24HR‐BTs (22.2% vs. 6.8%, p = 0.003) and PBTs overall (32.6% vs. 15.1%, p = 0.004). Overall median OS was 45 months. The association of PBT with shorter median OS appeared limited to first 24‐h transfusions (34 months 24HR‐BT vs. 48 months Postop‐BT vs. 53 months no‐PBT, p = 0.009) and was dose‐dependent, with a median OS of 52 months for 0 units 24HR‐BT, 35 months for 1 unit, and 25 months for ≥2 units ( p = 0.004). Independent predictors of OS included node‐positivity (hazard ratio [HR]: 1.93, p < 0.001), perineural invasion (HR: 1.64, p = 0.050), postoperative pancreatic fistula (HR: 1.94, p = 0.018), and 24HR‐BT (HR: 1.75, p = 0.001). Conclusions: Transfusions given within 24 h are associated with dose‐dependent decreases in survival after pancreatectomy for PDAC.